Adubação da mamoneira com NPK irrigada com água de esgoto doméstico tratado e água de poço. - Borges, Diêgo Silva (2011)
The experiment with the cultivation of castor bean (Ricinus communis L.) cultivar BRS 149 Northeast, was established and conducted under field conditions at the experimental station CAGECE / PROSAB / CT-CFU in the municipality of Aquiraz - CE, with the aim of evaluating the effect of interactions of NPK on yield components and yield. The experiment was a split plot with two plots, one irrigated with well water (AP) and the other with water from treated sewage (EDT), both with thirteen treatments including a control treatment. For the determination of yield components and yield were observed stem diameter, number of bunches per plant, seed number per bunch and weight of hundred seeds of six plants experimental treatment. Irrigation with well water treatment with the fertilizer-50N-60P2O5 50K2O kg ha-1 had the highest average for most of the variables, achieving productivity of 1908.6 kg ha-1 seed.